2016
DOI: 10.1021/acs.langmuir.6b02539
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stimuli Responsive Supramolecular Structures Based on Azobenzene Surfactant-Encapsulated Polyoxometalate

Abstract: Multi-stimuli responsive materials have attracted intense attention as extensive application prospect in many fields, yet achievement of multi-stimuli responsiveness remains a challenge. Herein, we report a tri-stimuli responsive supramolecular structure fabricated by a cationic surfactant, 4-ethyl-4'-(trimethylaminohexyloxy) azobenzene bromide (ETAB), and anionic Eu-containing polyoxometalates (Eu-POM), based on an ionic self-assembly (ISA) strategy. Following different responsive mechanisms, the resultant ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…AzoTAB surfactants have received significant attention for their potential applications, for example in the design of light-responsive gels [25][26][27] and DNA, [28][29][30] modified graphene oxide, [31][32] photomanipulation of droplets, 8 templating 33 and photoluminescent complexes. 34 In contrast, little has been done to determine the relationship between molecular design and function in AzoTABs. Hayashita et al studied the effect of the length of the hydrophobic segment (R1 + R2 < 10) of AzoTABs in the trans-and cis-forms and determined that an increase in the length of the alkyl tail (R1) led to a decrease in both the absolute conductivity and CMC.…”
Section: Introductionmentioning
confidence: 99%
“…AzoTAB surfactants have received significant attention for their potential applications, for example in the design of light-responsive gels [25][26][27] and DNA, [28][29][30] modified graphene oxide, [31][32] photomanipulation of droplets, 8 templating 33 and photoluminescent complexes. 34 In contrast, little has been done to determine the relationship between molecular design and function in AzoTABs. Hayashita et al studied the effect of the length of the hydrophobic segment (R1 + R2 < 10) of AzoTABs in the trans-and cis-forms and determined that an increase in the length of the alkyl tail (R1) led to a decrease in both the absolute conductivity and CMC.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both the morphology and structure were barely affected by Cu 2+ , indicating that the energy release from the O → W LMCT excited state transferred to Cu 2+ rather than the 5 D 0 emitting state of Eu 3+ is the possible reason for the fluorescence quenching. 58 Specifically, as Cu 2+ diffused into the solution and came close to the Eu 3+ ion surface, the energy transfer was more efficient for the smaller sized nanoparticles and externally distributed EuW 10 . 59…”
Section: Results and Discussionmentioning
confidence: 99%
“…The calculated interplanar distance of xerogel (1:1) was 4.26 nm, which is larger than that of pure C 20 IPS. It is known that the transverse and longitudinal lengths of EuW 10 are about 0.8 and 1.44 nm, respectively (Scheme b) . Given the water solubility and charged character, the EuW 10 tends to approach the hydrophilic head group of C 20 IPS.…”
Section: Resultsmentioning
confidence: 99%